Paradoxical evidence on ethnic inequities in child welfare: Towards a research agenda. (January 2019) - Bywaters, Paul; Scourfield, Jonathan; Webb, Calum; Morris, Kate; Featherstone, Brid; Brady, Geraldine; Jones, Chantel; Sparks, Tim
Abstract: This paper aims to compare developments in theory and evidence about ethnic disparities in the USA with findings from the Child Welfare Inequalities Project in England with a view to identifying key issues for a future research agenda. It has a particular focus on the relevance of the concept of the Hispanic Paradox for disparate intervention rates between ethnic populations in England. Three key theoretical dimensions for explaining such disparities are identified and outlined: artefactual, demand and supply factors. Findings from the study in England are then introduced to explore the relevance of these dimensions in a data set of over 14, 000 individual children who were either on child protection plans (with substantiated child abuse or neglect) or who were 'looked after children: in out-of-home care at the 31st March 2015. While some ethnic populations were experiencing much more difficult average socio-economic circumstances (SEC) than others (using deprivation scores for small neighbourhoods as a proxy measure of family SEC), such factors were only a partial explanation for differential intervention rates between ethnic groups. Overall, large differences in intervention rates were found between ethnic categories and sub-categories which also confounded simply attributing disparities to either cultural differences, such as family patterns, or to individual or institutionalised discrimination. The potential for cost saving if intervention rates could match those ethnic groups with the lowest levels of service use would be considerable. More research is needed to ensure that data is comprehensive, reliable and valid, that there is better understanding of how socio-economic factors affect service demand and what characteristics of different ethnic populations and different approaches o service provision contribute to differential intervention rates. Highlights: Most minority ethnic groups in England and USA experience socio-economic (SEC) disadvantage. Controlling for SEC, wide disparities in child protection rates found between ethnic categories. Indian rates lower than Pakistani, Bangladeshi, White British. Black African rates lower than Black Caribbean. More research is needed to build understanding and underpin policy and practice attention.